(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article is devoted to the study of the importance, types, and usage of function words in speech. It analyzes the role of function words in clarifying meaning, ensuring coherence, and enriching expression. The grammatical and stylistic aspects of function words are also examined